Estudo de indicadores de ciência, tecnologia e inovação (CT&I) e sua relação com a competitividade dos estados brasileiros com ênfase ao Pará - ABREU, Wendel Fialho de (Universidade Federal da Bahia, 2023)
Science, Technology and Innovation (STI) indicators support the implementation, monitoring, evaluation and improvement of strategies and public policies. This study compares and analyzes the STI measurement approaches of the World Intellectual Property Organization (WIPO), the Science, Technology and Innovation Ministry (MCTI), of the federal government, and the State Composite Indicator of Innovation (ICEI), it also evaluates the relationship of these indicators with the competitiveness of the Federation Units (UF) and municipalities, considering deposits of Intellectual Property (IP) assets, the Public Leadership Center (CLP) competitiveness rankings, Gross Domestic Product (GDP) and Human Development Index (HDI), emphasizing the Pará state. This research concluded that the national STI measurement model does not address critical issues highlighted in the international model, nor indicators of the effectiveness of public policies. It also evidenced regional imbalances, accentuated in Pará, and an interrelationship between innovative capacity, production and technological transfer and competitiveness of the states.